2016
DOI: 10.1186/s13054-016-1420-4
|View full text |Cite
|
Sign up to set email alerts
|

The effect of camicinal (GSK962040), a motilin agonist, on gastric emptying and glucose absorption in feed-intolerant critically ill patients: a randomized, blinded, placebo-controlled, clinical trial

Abstract: BackgroundThe promotility agents currently available to treat gastroparesis and feed intolerance in the critically ill are limited by adverse effects. The aim of this study was to assess the pharmacodynamic effects and pharmacokinetics of single doses of the novel gastric promotility agent motilin agonist camicinal (GSK962040) in critically ill feed-intolerant patients.MethodsA prospective, randomized, double-blind, parallel-group, placebo-controlled, study was performed in mechanically ventilated feed-intoler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 42 publications
1
33
0
Order By: Relevance
“…Due to concerns about side effects, we (AMD and MJC) recently completed 2 trials using a non‐macrolide motilin receptor agonist. In a single‐center study of 23 critically ill patients with established feed intolerance, a single dose of the motilin receptor agonist, camicinal, when compared with placebo, appeared to accelerate gastric emptying and increase carbohydrate absorption . In a subsequent international multicenter, parallel‐group, blinded, randomized controlled trial of 84 critically ill patients, preemptive administration of enteral camicinal did not significantly augment the provision of goal enteral nutrition .…”
Section: Drug Therapiesmentioning
confidence: 99%
“…Due to concerns about side effects, we (AMD and MJC) recently completed 2 trials using a non‐macrolide motilin receptor agonist. In a single‐center study of 23 critically ill patients with established feed intolerance, a single dose of the motilin receptor agonist, camicinal, when compared with placebo, appeared to accelerate gastric emptying and increase carbohydrate absorption . In a subsequent international multicenter, parallel‐group, blinded, randomized controlled trial of 84 critically ill patients, preemptive administration of enteral camicinal did not significantly augment the provision of goal enteral nutrition .…”
Section: Drug Therapiesmentioning
confidence: 99%
“…In healthy, ambulatory patients with gastroparesis and in the critically ill, erythromycin accelerates gastric emptying, via stronger and more frequent antral contractions, a reduction in the frequency of pyloric pressure waves and pyloric tone . However, at least in the critically ill, the effect of erythromycin to accelerate gastric emptying is most pronounced when the baseline gastric emptying rate is slow, and in the previous single‐center study, a dose of 75 mg camicinal did not appear to accelerate gastric emptying in a cohort of critically ill patients who had a relatively normal rate of emptying at baseline . Accordingly, an effect of camicinal may have been apparent if the patient cohort had slower gastric emptying at baseline.…”
Section: Discussionmentioning
confidence: 84%
“…Camicinal was designed to enhance the specificity for the recombinant human motilin receptor and avoid the adverse effects associated with the use of macrolide antibiotics. In a single‐center study of 23 critically ill patients with established feed intolerance, a single 50‐mg dose of camicinal (n = 15), when compared with placebo (n = 8), appeared to accelerate gastric emptying, quantified using an isotope breath test and increased carbohydrate absorption …”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, although the sample size was small, the findings of the present study confirm that camicinal has the expected effects of this class of agent on interdigestive motility in healthy humans by inducing gastric phase III contractions. In previous studies in healthy subjects, significant stimulation of gastric emptying rates was observed with a camicinal dose of 25 mg or higher …”
Section: Discussionmentioning
confidence: 86%
“…In addition, camicinal was shown to enhance gastric emptying rate acutely and during a 14 weeks treatment period in healthy volunteers . Furthermore, administration of 50 mg camicinal increased gastric emptying and subsequently glucose absorption in feed‐intolerant critically ill patients . Despite its stimulating effect on gastric emptying in humans, camicinal has no effect on esophageal function, small bowel, colonic, or whole gut transit times .…”
Section: Introductionmentioning
confidence: 99%